Young Doctors' Perception Of The Effectiveness Of The Clinical Learning System At Royal Prima Hospital Medan - Restin Julianti Zebua; Ermi Girsang; Sri Lestari Ramadhani Nasution (Jurnal Ners, 2025)
Young doctors often have different perceptions of the effectiveness of clinical learning in medical professional education. Clinical learning is a crucial stage in shaping the competence of young doctors, in terms of knowledge, skills, and professionalism. This study aims to explore young doctors' perceptions of the effectiveness of the clinical learning system at Royal Prima General Hospital in Medan. This qualitative study with a phenomenological approach involved six informants (five young doctors and one clinic coordinator) who were selected purposively. Data were collected through in- depth interviews, focus group discussions, and observations. The results of the study revealed four main themes. First, the quality of clinical learning is influenced by the clarity of instructions, tutor involvement, patient availability, and rotation structure. Second, the learning environment is influenced by the relationship with the supervisor and the clinical work atmosphere. Third, the young doctors' self-competence includes self-confidence, readiness to face patients, and stress management strategies. Fourth, supporting factors (senior support, hospital facilities) and inhibiting factors (patient case variations, high workload, differences in tutor supervision styles) also influence the effectiveness of clinical learning. In conclusion, the effectiveness of clinical learning is influenced by the interaction of instructional, personal, environmental, and structural factors. Therefore, improvement efforts are needed in the form of strengthening tutor supervision skills, equalizing practice opportunities, and providing psychosocial support for young doctors in order to optimize the clinical learning system.